2019
DOI: 10.1093/mnras/stz2069
|View full text |Cite
|
Sign up to set email alerts
|

The H i velocity function: a test of cosmology or baryon physics?

Abstract: Accurately predicting the shape of the Hi velocity function of galaxies is regarded widely as a fundamental test of any viable dark matter model. Straightforward analyses of cosmological N -body simulations imply that the ΛCDM model predicts an overabundance of low circular velocity galaxies when compared to observed Hi velocity functions. More nuanced analyses that account for the relationship between galaxies and their host haloes suggest that how we model the influence of baryonic processes has a significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…Recently, Lagos et al (2018) presented a new semi-analytic model of galaxy formation, S , with improvements over previous SAMs in the ability to reproduce galaxy scaling relations. Chauhan et al (2019) also recently showed that S is able to reproduce the HI mass-velocity width relation observed by the AL-FALFA survey. It is thus interesting to see if the tension between observations and simulations extends to the S implementation as well.…”
Section: Comparison With Semi-analytical Models Of Galaxy Formationmentioning
confidence: 80%
“…Recently, Lagos et al (2018) presented a new semi-analytic model of galaxy formation, S , with improvements over previous SAMs in the ability to reproduce galaxy scaling relations. Chauhan et al (2019) also recently showed that S is able to reproduce the HI mass-velocity width relation observed by the AL-FALFA survey. It is thus interesting to see if the tension between observations and simulations extends to the S implementation as well.…”
Section: Comparison With Semi-analytical Models Of Galaxy Formationmentioning
confidence: 80%
“…This simulation relies on the 'Synthetic Uni-veRses For Surveys' (SURFS) simulations of cosmic structure (Elahi et al 2018), the SHARK semi-analytic model of galaxy evolution (Lagos et al 2018) and the STINGRAY mock sky builder (Obreschkow et al, in prep.). This threestep approach is conceptually identical to that of Chauhan et al (2019), used for the ALFALFA survey. To cover the full dynamic range of H I masses, the reference simulation concatenates two cubic simulation boxes with volumes of 40 3 h −1 Mpc (micro-SURFS) and 210 3 h −1 Mpc (medi-SURFS), respectively (where h = 0.6751).…”
Section: Survey Predictionsmentioning
confidence: 99%
“…Mock H line profiles have also been used to reconcile the observed H velocity function with those obtained from cosmological simulations (e.g. Macciò et al 2016;Brooks et al 2017;Chauhan et al 2019).…”
Section: Introductionmentioning
confidence: 99%